THE ROLE OF INVESTMENT POTENTIAL IN THE CONDITIONS OF CRISIS MANAGEMENT OF THE NATIONAL ECONOMY - Tarchynets, O.S. (The actual problems of regional economy development, 2023)
In the article the analysis of the theoretical going is carried out near determination of concept of investment potential and certainly his value for crisis management of economy. In the modern terms of the crisis state of national economy, war-induced Russia against Ukraine, actuality is collected by the question of search of ways of overcoming of crisis consequences and the value of investment potential grows in the context of subsequent renewal of country in a post-war period.Obvious is insufficiency of own budgetary resources for overcoming of economic crisis, war-induced. Taking into account it, the increase of investment potential of Ukraine and use of him for the aims of crisis management a national economy can become the important instrument of renewal strategically. The purpose of the article is opening of theoretical aspects of interpretation of investment potential and its value for ancrisis management a national economy. Gaining end is carried out by the use of methods of analysis and synthesis, generalization and comparison. For today there are much going near essence interpretation of definition «investment potential». It is generalized possible to group them after such directions: resource, that determines investment potential exceptionally as an aggregate of present internal resources and powers of economic subjects.However taken into account such approach is not by potential of resources of outsourcings of bringing in; probabilistic, in accordance with which investment potential is interpreted as an aggregate of possibilities of investing, which are based on co-operation of factors and pre-conditions and represented in form investment streams; market approach consists in a credible necessity for capital investment in accordance with market conditions, that determines investment potential as a result of co-operation of demand and supply of investment resource at the marketin accordance with that, what terms can be offered investment project (profitability, risks, term of recoupment, and others like that);capacity, foresees determination of investment potential in the context of ability of research (territories, industries of economy, subject of menage) object to use a capital taking into account influence of internal and external factors;the structural examines investment potential as component element of the system of potentials of higher level (on a row with labour, innovative, resource – in composition economic); effective direction is determined by investment potential through ability of research object to get a certain result from bringing in of the proper resources.Thus the index of estimation of investment potential is foreseen by determination of maximal result, what object of research can get the use of present investment resources at terms. The multidimensionalness of interpretation of concept of investment potential testifies to his complication and importance for an antikrizovogo management a national economy. In the conditions of soldiery losses and budgetary deficit, exactly investments can become the key factor of proceeding in the Ukrainian economy. Thus, one of key tasks on a way to effective realization of investment potential in the conditions of crisis management an economy there is providing of financial, external economic, political and social equilibrium, which will allow to provide the stable terms of development of national economy and will stimulate the increase of investment resource on the basis of improvement of investment image, antishadow of economy and income of external investment capital.